PEMBERIAN PROTEIN ADHESIN 38-KILODALTON MYCOBACTERIUM TUBERCULOSIS PERORAL MENINGKATKAN JUMLAH MAKROFAG DAN LIMFOSIT USUS MENCIT BALB/c - Triliana, Rahma; Kartosen, Ade A; Puspitasari, Dianika P; Murwani, Sri; Santoso, Sanarto; Arthamin, Maimun Z (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2018)
Tuberculosis (TB), caused by Mycobacterium tuberculosis (M.tb), is one of the world health problems. Oral vaccination of M.tb has a potential to reduce the risk and complication of TB. The 38-kDa adhesin protein as one of oral TB vaccine candidates has not been proven. This study is aimed to determine M.tb 38-kDa adhesin protein effect on macrophage and lymphocyte numbers in mice intestine after an oral administration. BALB/c mice (n=20), age 6–8 weeks, and were divided into 4 groups: control (K), adjuvant (A), 38-kDa 100Î¼g adhesin protein (P), and combination of 100Î¼g 38-kDa adhesin protein with adjuvant (PA). An oral administration was given at the beginning with 2 boosters every 4 weeks. After 3 days of the second booster, the mice were killed and the intestine was taken and stained with haematoxylin eosin (HE) to measure its macrophages and lymphocytes number. The mean ±2SD were 18.4 (3.71) and 6.09 (0.34), 23.0 (7.78) and 8.86 (1.19), 42.2 (13.63) and 23.49 (3.91), 95.4 (30.11), and 53.57 (13.79) respectively for K, A, P and PA group. The statistical test showed a significant difference among each group revealing the role of M.tb 38-kDa adhesin protein as immunogenic inducing cellular immunity in intestine. In this study, so far it was found that the oral administration of M. tb 38-kDa adhesin protein has an ability to increase macrophage and lymphocyte numbers in the mice intestinal BALB/c.